Clinicopathological Study on Cutaneous Vasculitis (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Cutaneous vasculitis is an inflammatory process directed primarily at vessels which results in the destruction of the vessel walls leading to hemorrhage, ischemia, and/or infarction. Cutaneous involvement in cutaneous vasculitis may be primary or reflector of a systemic disease.Aim: To find out the aetiology and clinicopathologic features of cutaneous vasculitis in Chattogram costal area.Methods: A total of 50 patients diagnosed clinically and confirmed histologically as cutaneous vasculitis were selected for this descriptive cross-sectional study from March 2016 to August 2017. Detailed history, clinical examination and the baseline investigations along with special tests such as Antinuclear antibodies (ANA) profile, Antineutrophil Cytoplasmic Antibodies (ANCA) and Antistreptolysin O (ASO) titer were conducted in all patients.Results: Out of 50 cases, 20% of the patients had (Henoch-Schonlein purpura) HSP and 10% had Urticarial vasculitis (UV), collagen vascular disease associated vasculitis were present in 2%, Cutaneous polyarteritisnodosa (C-PAN), eosinophilic vasculitis and nodular vasculitis were present in 4% of the patients each. Rests of the patients (54%) were designated as idiopathic cutaneous small vessels vasculitis (SVV). The commonest lesion was palpable purpura. Infection was the commonest cause of cutaneous vasculitis for about 22%, followed by drugs (20%), malignancy (2%) and connective tissue disease (2%). Two patients with HSP had positive ANCA, 3 without any overt manifestations and 1 with systemic sclerosis. Histologically Leukocytoclastic vasculitis (LCV) was the commonnest pattern (72%), lymphocytic in 20%, granulomatous in 4% and eosinophilic vasculitis in 4% of patients.Conclusion: Cutaneous SVV is the commonest form of vasculitis. The heterogenecity of this group of disorders is well represented in this study. To reach an etiological diagnosis of vasculitis, clinical and pathological features need to be correlated and supplemented by laboratory investigations.JAFMC Bangladesh. Vol 15, No 1 (June) 2020: 61-64